Analisis Life Cycle Assessment (LCA) Pada Pengolahan Air Limbah di Pahu Makmur Palm Oil Mill: Life Cycle Assessment (LCA) Analysis of Wastewater Treatment at Pahu Makmur Palm Oil Mill - DWI ERMAWATI RAHAYU; EDHI SARWONO; M IBNU ALFARIDHO (BRIN Publishing (Penerbit BRIN), 2023)
ABSTRACT One of the potential wastes generated by the Crude Palm Oil (CPO) production process is Palm Oil Mill Effluent (POME). POME wastewater can produce Greenhouse Gases (GHG) and high levels of organic materials such as COD, BOD, and total nitrogen, which have impacts on the environment. This study aims to analyse the environmental impacts of POME wastewater treatment using the Life Cycle Assessment (LCA) method based on SNI ISO 14040:2016. The LCA analysis was aided by SimaPro v 9.3.0 software using the IMPACT 2002+ calculation method. The research focuses on measuring the environmental impacts of the POME waste treatment process in a 1 ton CPO production unit, with impact categories including global warming, water eutrophication, and respiratory organics. The research limitation is set to